Understanding the bottlenecks in methodological adoption of constructivism in secondary schools in Kenya - Gideon Mwanda; Ronnie Midigo (University of Muhammadiyah Malang, 2019)
Constructivist teaching and learning approach is one of teaching approach gaining popularity based on its principles of learner centered education. This study investigated the effectiveness of constructivist method of instruction on learning biology and challenges facing its implementation in secondary school students. The study design was quasi-experimental non-equivalent groups with a post-test examination. A total sample participated in this study was 477 students and 12 teachers. The instruments used in this study were; constructivist instruction manual, post-test, attitude questionnaire, and teacher’s questionnaire. The data collected was analyzed descriptively using mean and standard deviation values, while t-test and ANOVA were used to test the differences between group means at α=0.05 level. The study established that constructivist method of instruction was more effective in learning biology compared to conventional methods. Moreover, the both positive learner and negative teacher attitudes toward the application of constructivism was found as considerable as inadequate compulsory facilities in the implementation of constructivist learning approach. Thus, it is recommended to conduct deliberate programs in implementing constructivist learning approach in secondary schools in Kenya.